The Relationship between the Use of Renewable Energies and the Dimensions of Sustainable Development in Algeria during the Period 1990-2014 - Hadj Khelifa; Djilali Mezouaghi; Hamid Bachouche (Advanced Research in Economics and Business Strategy Journal)
This study aimed to determine the relationship between the transition to the use of renewable energy and sustainable development in Algeria during the period 1990-2014, across three dimensions: economic, social, and environmental. Simple regression models and SPSS.V Software 22.0 were used. The study found that there was a significant relationship between the transition to the use of renewable energy and the economic dimension of sustainable development, as represented by the gross domestic product (GDP). However, the study found that there was no significant relationship between the consumption of renewable energies and the social dimension of sustainable development, as represented by the Human Development Index (HDI). The results also showed that there was a significant relationship between the use of renewable energies and the environmental dimension of sustainable development, as represented by the emission of carbon dioxide (CO2).